2018
DOI: 10.1093/ofid/ofy210.313
|View full text |Cite
|
Sign up to set email alerts
|

302. Role of Inflammatory Markers in Diagnosing Diabetic Foot Infection: A Meta-Analysis

Abstract: BackgroundDiabetic foot ulcers (DFUs) cause significant morbidity and put great economic burden on patient and healthcare facilities. Infection is the main driving force behind admissions related to DFU. Culture of soft tissue or bone is invaluable in diagnosing infection but is time consuming. Inflammatory markers including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and procalcitonin (PCT) are rapid, simple, and inexpensive laboratory tests that can aid in early diagnosis of diabetic foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Many inflammatory markers such as CRP, ESR, procalcitonin and WCC have been extensively investigated as diagnostic markers in the setting of diabetic foot infection. 16 Each of these markers was found to be significantly associated to the severity of infection with different reported thresholds. However, very few studies researched basic haematological blood elements as performance tools for infection severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many inflammatory markers such as CRP, ESR, procalcitonin and WCC have been extensively investigated as diagnostic markers in the setting of diabetic foot infection. 16 Each of these markers was found to be significantly associated to the severity of infection with different reported thresholds. However, very few studies researched basic haematological blood elements as performance tools for infection severity.…”
Section: Discussionmentioning
confidence: 99%
“…The current IWGDF guidelines to diagnose osteomyelitis are based on a combination of tests which includes C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR), procalcitonin, plain X‐ray, magnetic resonance imaging (MRI), probe‐to‐bone and bone biopsy 4 . Besides the MRI and the golden test of bone biopsy which both have high rates of sensitivity and specificity, the inflammatory markers such as CRP, ESR, procalcitonin and white cell count (WCC) have been extensively studied to differentiate between non‐infected and infected DFU 16 . However, few studies investigated the performance of WCC when differentiating between infected DFU with and without osteomyelitis 17–19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly elevated ESR (≥70 mm/h) has a sensitivity, specificity, and AUC for the diagnosis of DFO of 81%, 80%, and 0.84, respectively. 62 Compared with ESR, CRP levels tend to rise more quickly with infection and fall more quickly with the resolution of infection. Serum values of CRP have consistently been found to be significantly higher in infected than noninfected DFUs and in patients with noninfected DFU than in those with no foot ulcer, with levels increasing significantly with the severity of infection.…”
Section: Rationalementioning
confidence: 99%
“…Serum values of CRP have consistently been found to be significantly higher in infected than noninfected DFUs and in patients with noninfected DFU than in those with no foot ulcer, with levels increasing significantly with the severity of infection. 62,63 Compared to WBC and ESR, CRP has shown higher diagnostic accuracy for grade 2 (infected) DFU. 63 Studies of serum PCT levels have also found that levels were significantly higher in infected DFU than noninfected DFU, but there was little correlation between the values and the infection severity.…”
Section: Rationalementioning
confidence: 99%